Confronting policy myopia: Short‐term government policy and information seeking behaviors in rural Thailand. - Setthasuravich, Prasongchai; Kato, Hironori (Review of Policy Research, 2026)
Short‐term policy (STP) has attracted considerable attention as a form of time‐related public policy and is typically used to solve urgent problems. The objective of this study, which considers STP as policy myopia from an information science perspective, is to discuss the challenges encountered during the STP policymaking process and their impact on the effectiveness of information dissemination to the public, and the barriers to information seeking behavior (ISB) among rural residents during STP implementation, alongside their methods of seeking STP information. This study uses the first car buyer policy (FCBP) in Thailand as a case study. Semistructured interviews were conducted with five government officials and 39 rural residents in December 2019. A qualitative analysis, facilitated by ATLAS.ti software, involved an iterative coding process to develop thematic categories that emerged directly from the data, ensuring a grounded understanding of ISB and policy dissemination challenges. The findings of this study show that the dissemination of government information and its consequences are the main issues in the STP process. They also reveal that the ISB of rural residents is related to limited time resources, concerns about government policy, and substandard Internet access as obstacles or intervening factors. Based on these findings, this study provides theoretical and policy implications that can enrich STP and ISB in developing countries. From a theoretical standpoint, it introduces a novel conceptual framework that integrates policy myopia within the information behavior model, highlighting how STP influences ISB, particularly in rural areas. Additionally, this study provides practical insights for policymakers by identifying key barriers to information access and offering strategies to enhance communication effectiveness. The insights gained from this study can inform future policy design, showing that governments should enhance information dissemination, adapt communication channels to audience needs, tailor information to local contexts, and support active ISB among rural residents through targeted awareness campaigns and infrastructure improvements.